THE ARTICULATE MAMMAL: AN INTRODUCTION TO PSYCHOLINGUISTICS (Author: Jean Aitchison) - Scovel, Thomas (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 1980)
Jean Aitchison. THE ARTICULATE MAMMAL: AN INTRODUCTION TO PSYCHOLINGUISTICS. New York: Universe Books, 1977. 256 pp. (also available in paperback editions from London: Hutchison & Co. Ltd., 1978, £3.25; and New York: McGraw-Hill Book Co., 1978, $4.50.)